Simulation of Probe Position-Dependent Electron Energy-Loss Fine Structure. (31st March 2014) - Oxley, Mark P.; Kapetanakis, Myron D.; Prange, Micah P.; Varela, Maria; Pennycook, Stephen J.; Pantelides, Sokrates T.
Abstract: We present a theoretical framework for calculating probe-position-dependent electron energy-loss near-edge structure for the scanning transmission electron microscope by combining density functional theory with dynamical scattering theory. We show how simpler approaches to calculating near-edge structure fail to include the fundamental physics needed to understand the evolution of near-edge structure as a function of probe position and investigate the dependence of near-edge structure on probe size. It is within this framework that density functional theory should be presented, in order to ensure that variations of near-edge structure are truly due to local electronic structure and how much from the diffraction and focusing of the electron beam.